Uncharted territory: measuring costs of diagnostic errors outside the medical record. Issue 11 (7th July 2012) - Schwartz, Alan; Weiner, Saul J; Weaver, Frances; Yudkowsky, Rachel; Sharma, Gunjan; Binns-Calvey, Amy; Preyss, Ben; Jordan, Neil
Abstract : Context: In a past study using unannounced standardised patients (USPs), substantial rates of diagnostic and treatment errors were documented among internists. Because the authors know the correct disposition of these encounters and obtained the physicians' notes, they can identify necessary treatment that was not provided and unnecessary treatment. They can also discern which errors can be identified exclusively from a review of the medical records. Objective: To estimate the avoidable direct costs incurred by physicians making errors in our previous study. Design: In the study, USPs visited 111 internal medicine attending physicians. They presented variants of four previously validated cases that jointly manipulate the presence or absence of contextual and biomedical factors that could lead to errors in management if overlooked. For example, in a patient with worsening asthma symptoms, a complicating biomedical factor was the presence of reflux disease and a complicating contextual factor was inability to afford the currently prescribed inhaler. Costs of missed or unnecessary services were computed using Medicare cost-based reimbursement data. Setting: Fourteen practice locations, including two academic clinics, two community-based primary care networks with multiple sites, a core safety net provider, and three Veteran Administration government facilities. Main outcome measures: Contribution of errors to costs of care. Results: Overall, errors in care resulted in predicted costs of approximately $174 000 across 399 visits, of which only $8745 was discernible from a review of the medical records alone (without knowledge of the correct diagnoses). The median cost of error per visit with an incorrect care plan differed by case and by presentation variant within case. Conclusions: Chart reviews alone underestimate costs of care because they typically reflect appropriate treatment decisions conditional on (potentially erroneous) diagnoses. Important information about patient context is often entirely missing from medical records. Experimental methods, including the use of USPs, reveal the substantial costs of these errors.